Comparison of the effects of Pb treatment on thylakoid development in poplar and cucumber plants - Sárvári Éva (Acta biologica Szegediensis, 2002)
Pb (10 to 100 uM ) effects on the development of thylakoids were investigated in Fe-EDTA an d Fe-citrate grown cucumber and poplar to compare the symptoms in different plant species. Increased chlorophyll content of leaves appeared either in PSII core or LHCII depending on the treatment. Lowering of the chlorophyll content, however, was accompanied by decrease in PSI and LHCII, and relatively high stability of PSII core. PSII efficiency and C02 fixation were mostly unchanged or decreased moderately, but rise in the non-photochemical quenching was observed in all kinds of treatment. While Pb could not be detected and Mn content decreased in poplar leaves, changes in photosynthetic parameters paralleled with the Pb content in cucumber, and increase in Fe, Mn, and Ca content was measured. The direct effects of Pb or oxidative stress may evoke the changes in cucumber, while Pb induced Mn deficiency seems to play a role in poplar. Alterations in the composition of thylakoids were probably triggered by regulatory processes, which optimise the structure and function under stress conditions.